Attacks on the United States: Index, Icons and Intericonicity in Photojournalism - Jane BAYLY (E-REA)
Despite the fact that deadly attacks on the United States involving large numbers of innocent people are quite rare in its history, photographic coverage suggests a general similarity even though each event is unique in its particularity. Through the example of news photographs taken with the primary goal of informing the American readers about the most deadly attacks on the United States since World War II, this paper will first demonstrate through the coverage of the events of the Oklahoma City Bombing (1995), the attack on the Twin Towers of the World Trade Center (2001), and the bombing during the Boston Marathon (2013), that the news media tends to visually condense events into a few photo-categories (Chéroux 19-24). We will then identify the most frequently circulated images of the attacks that the news media tended to transform into icons and explain how it made use of intericonicity to render ideologically charged photographic messages easily and rapidly accessible to the news audience.